2014
DOI: 10.1111/nhs.12192
|View full text |Cite
|
Sign up to set email alerts
|

Internet addiction and physical and psychosocial behavior problems among rural secondary school students

Abstract: The aim of this study was to determine secondary school students' levels of Internet addiction and the physical and psychosocial behavior problems they face while using the Internet. This descriptive study was conducted in three state secondary schools in a rural area in the western part of Turkey. This study's sample consisted of 549 students who agreed to participate, with the consent of their families, and who had an Internet connection at home. The data were evaluated using t-tests and variance analyses. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 22 publications
2
27
0
1
Order By: Relevance
“…According to Polos's study, there is a relationship between the use of Sleep Time-Related Information and Communication Technology (STRICT) and impairments in sleep patterns and daytime functioning in adolescents 33 . There are also studies that have reported a correlation between IA and insomnia 3,5,15,34,35. Similarly, adolescents that use the internet for prolonged periods were reported as they were sleeping less and feeling overtired 16 . On the other hand, it was observed that the number of studies on the relationship between internet usage and problems with physical health or sleep are rare 5,36 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Polos's study, there is a relationship between the use of Sleep Time-Related Information and Communication Technology (STRICT) and impairments in sleep patterns and daytime functioning in adolescents 33 . There are also studies that have reported a correlation between IA and insomnia 3,5,15,34,35. Similarly, adolescents that use the internet for prolonged periods were reported as they were sleeping less and feeling overtired 16 . On the other hand, it was observed that the number of studies on the relationship between internet usage and problems with physical health or sleep are rare 5,36 .…”
Section: Discussionmentioning
confidence: 99%
“…In many studies, a direct correlation has been shown between psychological problems and Internet addiction 16,22,24,40 . According to the study results of Nalwa & Anand, adolescents have reported that life is very boring without the Internet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PIU has also been associated with impairment in various life domains, including problems with social relationships [4,7,30,43,[60][61][62] and professional endeavors. [7,12] PIU has also been linked to lower reported life satisfaction and well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Aksüt ve Batur'un (2007) çalışmasında erkeklerin haftada ortalama 12 saat, kızların 9 saat internet kullandıkları bulunmuştur. Cinsiyetin problemli internet kullanımının önemli bir yordayıcısı olduğu, erkeklerin kadınlara göre internet bağımlılığına daha yatkın (Özkan, 2013) ya da internet bağımlısı olma oranlarının daha yüksek olduğu görülmektedir (Canan et al, 2012;Dinçer, 2016;Gür, Yurt, Bulduk & Atagöz, 2015). Günümüzde ergenler, internetle küçük yaşlarda tanışmaktadır.…”
Section: Introductionunclassified